PENERAPAN APLIKASI ARCGIS DALAM PEMBUATAN PETA LOKASI DESA RIDOMANAH - Saktiyoso, Teguh; Dian Ekawati, Fatimah; Supratno, Setyo (Universitas Islam 45 Bekasi, 2024)
Location map is a location image that shows related locations on the earth's surface, location maps are made using a certain projection system so that they can be presented in a flat plane. The function of the location map is to show the size of the area, distance and direction of a place on the earth's surface. This map is made for comparison with the existing map in 2020. Ridomanah Village needs a location map so that it can compare with the existing location map with 2020 and compare with 2024 whether there is an expansion or widening of the distance, therefore the latest location map is made so that it can be clearly seen the area and distance of Ridomanah Village. The ArcGIS application has high capabilities in making digital maps to spatial analysis. The community service method applies science and technology diffusion by utilising the ArcGIS application combined with the socialisation method. The impact of community service is that the community and village officials can find out the distribution of the population, find out the distribution of production forests.